Evaluating the student experience with enrolment assistance in an integrated student support service program at the University of Southern Queensland. - Thangavelu, Anbarasu; Partridge, Helen; Carey, Kathy; O'Sullivan, Carmel; Lutvey, Naomi (Student Success v.10 n.1 p.99-114 https://doi.org/10.5204/ssj.v10i1.1121, 2019)
Interviews with students who accessed enrolment support were undertaken to explore reasons students utilised this service, and how integrated student support service models can impact on student transition, retention and success. Results indicate that students primarily required support with course enrolments because of the new environment they were studying in, not being accustomed to existing processes and a lack of confidence. In addition, along with the existing service model, the integration of enrolment support into the student support service model had a positive impact on the student experience and engagement. The implications of these findings for the tertiary education sector are considered in light of the increasing focus on student engagement and success. [Author abstract]